Optimizing Listening Skills with the ZIELTS Application: A Technological Approach to IELTS Success - Desri Maria Sumbayak; Alemina Br. Perangin-Angin; Vivi Adryani Nasution; Indah Putri Tamala; Rosalyn Magdalena Br. Sitorus; Fahri Afandi; Rania Alifiandra Matulatuwa (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2026)
Purpose of the Study: 1. To assess how the ZIELTS application affects candidates' performance in the IELTS listening section; 2. To identify key features of the ZIELTS application that enhance listening skills; 3. To evaluate candidates' perceptions of the ZIELTS application's effectiveness.Methodology: A mixed-methods design was adopted combining quantitative performance measurement and qualitative feedback analysis. Ten participants were randomly selected and assessed using pre- and post-tests to evaluate listening competence. Participants practiced listening using the ZIELTS application for two weeks and recorded the frequency of use and topic preferences in logbooks. Quantitative data were analyzed using descriptive statistics and a paired-samples t-test in SPSS, while qualitative data from logbooks and Focus Group Discussions (FGD) were examined through thematic analysis.Main Findings: The outcome revealed a modest but not statistically significant improvement in listening skills: the mean band score increased from 6.75 to 6.90, t(9) = 0.896, p = 0.394. While there was some variation in the progress of individual participants, users were satisfied with the user-friendly design of the application, the wide range of topics, and additional features like vocabulary lists and audio transcripts. Minor technical issues (e.g., inconsistencies between audio and text) were identified as opportunities for future enhancements.Novelty/Originality of This Study: This study is one of the earliest empirical explorations of ZIELTS, a purpose-built, exam-aligned AI application launched in March 2024, as a means of improving IELTS listening performance. Using a mixed-methods approach that integrates quantitative pre- and post-test assessments with qualitative learner feedback, it contributes original, context-specific evidence to the relatively under-researched intersection of AI-assisted language learning and IELTS listening preparation.